Penerapan Teknologi Tenaga Surya untuk Meningkatkan Penerangan dalam Aktivitas Ekonomi di Desa Cupak - Mochammad Syafiuddin Shobirin; Nuryana Adi Parta; Sahri Sahri; Bambang Wahrudin (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Cupak Village faces serious challenges related to the availability of adequate lighting, particularly in supporting the community's economic activities. Limited access to stable electricity has led to decreased productivity, especially at night, hindering various business operations. In addition, challenges in providing and maintaining conventional lighting systems, such as high operational costs and inadequate infrastructure, have worsened the situation. This community service project aims to implement solar technology as a sustainable alternative solution to increase the availability of lighting in Cupak Village. The approach used in this project is the installation of solar panels at several strategic points in the village, serving as the main lighting at night, especially in locations that support the community's economic activities. The community service process involves several stages, including the socialization of solar technology to the community, technical training in the installation and maintenance of solar power systems, and evaluation of the impact of this technology on the community’s economic productivity. The results of the project show that the implementation of solar technology has significantly increased the availability of lighting in Cupak Village. Villagers reported increased productivity in small businesses such as night trading and agricultural processing. In addition, the use of solar technology has proven to be more efficient and environmentally friendly compared to conventional lighting systems. This project successfully provides a long-term solution that not only boosts economic activities but also improves the quality of life for the people of Cupak Village.